The Impact of Interdisciplinary Team-Based Care on the Care and Outcomes of Chronically Ill Patients: A Systematic Review - Kongkar R; Ruksakulpiwat S; Phianhasin L; Benjasirisan C; Niyomyart A; Ahmed BH; Puwarawuttipanit W; Chuenkongkaew WL; Adams J (Journal of Multidisciplinary Healthcare, 2025)
Ruttanaporn Kongkar,1 Suebsarn Ruksakulpiwat,1 Lalipat Phianhasin,1 Chitchanok Benjasirisan,1 Atsadaporn Niyomyart,2 Bootan Hasan Ahmed,3 Wimolrat Puwarawuttipanit,1 Wanicha L Chuenkongkaew,4 Jon Adams5 1Department of Medical Nursing, Faculty of Nursing, Mahidol University, Bangkok, Thailand; 2Ramathibodi School of Nursing, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 3Frances Payne Bolton School of Nursing, Case Western Reserve University, Cleveland, OH, USA; 4Department of Ophthalmology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 5School of Public Health, The University of Technology Sydney, Sydney, NSW, AustraliaCorrespondence: Suebsarn Ruksakulpiwat, Email suebsarn25@gmail.comObjective: To examine the impact of interdisciplinary team-based care (ITBC) on chronically ill patients and their outcomes as reported in relevant contemporary literature.Methods: In this systematic review, PubMed, MEDLINE, Web of Science, CINAHL Plus Full Text, and ten publishers were searched to identify studies published between 2019 and 2024. Titles, abstracts, and full texts were screened for eligible studies and assessed for relevance. Inclusion and exclusion criteria were implemented to ensure that only studies relevant to our objective were included. The convergent integrated analysis framework suggested by the Joanna Briggs Institute was utilized for data synthesis.Results: Ten studies were included in the systematic review. Data synthesis revealed five major themes at different levels: 1) Patient level, including themes of Patients’ Self-Improvement and Patients’ Health Outcomes; 2) Interpersonal level, including themes of Providers’ Work Performance and Shared Decision Making; and 3) Organizational level, including the theme of Healthcare Utilization.Conclusion: ITBC has a significant positive impact on chronically ill patients at multiple levels. At the patient level, it enhances self-management and health outcomes. At the interpersonal level, it improves healthcare providers’ performance and promotes shared decision-making. At the organizational level, it leads to more efficient healthcare utilization.Keywords: interdisciplinary team-based care, chronic illness, patient outcomes, systematic review